2009
DOI: 10.3354/dao02032
|View full text |Cite
|
Sign up to set email alerts
|

Pathology, isolation and molecular characterisation of a ranavirus from the common midwife toad Alytes obstetricans on the Iberian Peninsula

Abstract: We describe the pathology, isolation and characterisation of a virus responsible for an outbreak of a systemic haemorrhagic disease causing high mortality in tadpoles of the common midwife toad Alytes obstetricans in the 'Picos de Europa' National Park in northern Spain. The virus, provisionally designated as the common midwife toad virus (CMTV), was isolated from homogenates of visceral tissue from diseased toad tadpoles following inoculation on epithelioma papulosum cyprini (EPC) cells. Molecular characteris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
50
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
2
2
2

Relationship

0
6

Authors

Journals

citations
Cited by 50 publications
(51 citation statements)
references
References 33 publications
1
50
0
Order By: Relevance
“…In amphibians, outbreaks of ranaviral disease are most often observed in larvae and recently metamorphosed animals (Green et al 2002 ;Docherty et al 2003 ;Balseiro et al 2009Balseiro et al , 2010; however, outbreaks that include adult animals are increasingly recognized (Cunningham et al 2007 ;Cheng et al 2014 ). Moreover, Earl and Gray ( 2014 ) demonstrated that ranavirus-associated mortality of larvae or metamorphs was suffi cient to cause population declines in highly susceptible species.…”
Section: Field and Clinical Findingsmentioning
confidence: 99%
See 1 more Smart Citation
“…In amphibians, outbreaks of ranaviral disease are most often observed in larvae and recently metamorphosed animals (Green et al 2002 ;Docherty et al 2003 ;Balseiro et al 2009Balseiro et al , 2010; however, outbreaks that include adult animals are increasingly recognized (Cunningham et al 2007 ;Cheng et al 2014 ). Moreover, Earl and Gray ( 2014 ) demonstrated that ranavirus-associated mortality of larvae or metamorphs was suffi cient to cause population declines in highly susceptible species.…”
Section: Field and Clinical Findingsmentioning
confidence: 99%
“…1a, b ). Hemorrhages are most often present on the ventral surfaces near the vent, rear legs, and gular regions, but can also be observed around the eyes, ear drum, tongue, tail, and feet (Balseiro et al 2009 ;Cheng et al 2014 ;Cunningham et al 2007 ;Docherty et al 2003 ;Geng et al 2010 ;Kik et al 2011 ;Meng et al 2014 ;Sutton et al 2014a ). Raised skin plaques or polyps have been described in tiger salamanders ( Ambystoma tigrinum ) and Chinese giant salamanders (Jancovich et al 1997 ;Bollinger et al 1999 ;Geng et al 2010 ).…”
Section: Amphibiansmentioning
confidence: 99%
“…Common midwife toad virus (CMTV) was fi rst isolated from common midwife toad tadpoles experiencing a mass mortality event in 2007 in northern Spain (Balseiro et al 2009 ). A second mass mortality event during 2008 in the same region of Spain involving CMTV affected common midwife toad tadpoles and juvenile alpine newts ( Mesotriton alpestris ; Balseiro et al 2010 ).…”
Section: Other Amphibian Ranavirusesmentioning
confidence: 99%
“…There are three recognized species of ranaviruses that are known to infect amphibians: FV3, ATV, and BIV. Also, there are several other ranaviruses that have been isolated from amphibians (e.g., common midwife toad virus, CMTV; Balseiro et al 2009 ), but are not currently recognized as ranavirus species. As discussed in Jancovich et al ( 2015 ), declaring a given isolate as a unique viral species is complex, and compounded by the fact that there is considerable sequence conservation, often greater than 95 % at the amino acid level among many ranavirus isolates.…”
Section: Ranaviruses Infecting Amphibiansmentioning
confidence: 99%
“…Currently, three amphibian ranaviruses have been identified: frog virus 3 (FV3), Bohle iridovirus (BIV) and Ambystoma tigrinum virus (ATV) [57]. Mortality events and/or infections involving viruses have been detected in amphibian population across the globe [58][59][60][61][62][63][64][65][66][67][68]. While ranavirus infections have been detected in both adult and larval amphibians, the virus appears to be most lethal in larvae [69].…”
Section: Three Host -Pathogen Systems (A) Amphibian Ranaviruses (I) Omentioning
confidence: 99%